2017
DOI: 10.5812/ccn.10655
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Family-Centered Care on the Duration of Weaning From Mechanical Ventilation in Coronary Artery Bypass Surgery Patients: A Clinical Trial Study

Abstract: Background: The use of nonpharmacological methods has been emphasized in the recent years. These methods are used to decrease the duration of weaning from mechanical ventilation after coronary artery bypass graft (CABG) surgery. Objectives: The present study aimed at determining the effect of family-centered care on the duration of weaning from mechanical ventilation in patients undergoing CABG. Methods: This clinical trial study was conducted in Jamaran Heart Subspecialty hospital in Tehran in 2016. Initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Improving family and patient satisfaction, 22 increasing self-efficacy, improving quality of life, 23,24 improving the information flow and interactions between families and treatment professionals, 25 helping intensive care patients to be aware of the care process, giving them relaxation and a sense of security, 26 improving communication between patient and family, achieving improved treatment outcomes, [27][28][29] acquiring a sense of re-control in family management, 30 reducing nursing job burnout, 31 creating a more effective relationship, increasing holistic nursing, 18,32 and reducing depression and fatigue among caregivers, 13,33,34 are the results extracted from studies on family-centered healthcare.…”
Section: Antecedents and Consequencesmentioning
confidence: 99%
“…Improving family and patient satisfaction, 22 increasing self-efficacy, improving quality of life, 23,24 improving the information flow and interactions between families and treatment professionals, 25 helping intensive care patients to be aware of the care process, giving them relaxation and a sense of security, 26 improving communication between patient and family, achieving improved treatment outcomes, [27][28][29] acquiring a sense of re-control in family management, 30 reducing nursing job burnout, 31 creating a more effective relationship, increasing holistic nursing, 18,32 and reducing depression and fatigue among caregivers, 13,33,34 are the results extracted from studies on family-centered healthcare.…”
Section: Antecedents and Consequencesmentioning
confidence: 99%
“…Safaeepour et al [ 4 ] studied the effect of family-centered care on weaning from MV in patients undergoing coronary artery bypass surgery. They showed longer weaning in patients whose family members were present at their bedside immediately after their admission to the cardiac ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the mechanically ventilated patients experience a lot of anxiety and stress because they are treated aggressively, do not have many visitors, and are in a loud and strange place, which can make them reliant on MV. For those admitted to ICUs, sensory deprivation caused by the absence of family visits can lead to a greater reliance on MV [ 4 ]. Happ et al [ 5 ] conducted a qualitative study and showed that families, who were present at the patient’s bedside during the weaning process, communicated with them through physical contact, touching, kissing and even supervision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the most important need of the families of patients admitted to the coronary intensive care were related to assurance and information (Coelho et al, 2022). Family presence and participation were found to be helpful in reducing the patients' anxiety, improving communication (Coelho et al, 2022) and stabilising haemodynamic and respiratory indicators, such as blood pressure, pulse rate and respiratory rate (Lolaty et al, 2014); this was also found to be effective in reducing ventilator withdrawal time and complications due to positive pressure (Safaeepour et al, 2017). Haemodynamic and respiratory indicators such as blood pressure, pulse rate, respiratory rate, in the ICU are essential for preventing organ failure by ensuring stability between oxygen delivery and demand in the relevant tissues (Majumdar, 2017).…”
Section: Introductionmentioning
confidence: 99%